Assessment of knowledge about stem cells among the expectant parents - Jarzyńska, Paulina; Janiszewska, Mariola; Firlej, Ewelina; Pawlikowska-Łagód, Katarzyna; Dąbska, Olga (Journal of Education, Health and Sport, 2017)
Introduction. Stem cells have different reproducibility, differentiation and proliferation. Due to the biological properties are mainly used in hematological diseases. We are seeing the phenomenon of the utilization of umbilical cord blood, which is increasingly being treated as "waste". Aim. The aim of this study was to assess the knowledge about stem cells among prospective parents. Material and methods. The study group consisted of 89 people waiting for the birth of a child. The study was conducted using a questionnaire own. The research material was collected through the website ankietka.pl Results. The vast majority of respondents (80.9%) declared that knows what they are stem cells while (74.1%) of the respondents showed knowledge of their application. Only every third respondent as a source of knowledge about stem cell pointed to a doctor or midwife. On the other hand (62%) of respondents rated that stem cells are valuable and important. Nearly every second had no knowledge of what the tanker compatibility between recipient and donor transplant of stem cells from umbilical cord blood. Conclusions. The results show that half of the respondents know what they are stem cells and what is their application. Less than half of the respondents showed knowledge of the procedures for obtaining stem cells. The vast majority of respondents more knowledgeable presented in terms of their storage and use. Clearly the results of the study showed that self-knowledge on stem cells among parents-does not reflect the real state of the information. Health education of future parents is still insufficient. Visible is the increase in misuse of stem cells from umbilical cord blood.